Dampak Mengkonsumsi Alkohol terhadap Perilaku Sosial Remaja - Farisi, Muhammad Fariz Al; Pratiwi, Rezika Pratiwi; Firmansyah, Muhammad Firmansyah; Isnaini, Maya Insnaini; Sarman, Freddi (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
Abstract : Consumption of alcoholic beverages has become a status symbol for teenagers. Alcohol as we know is an addictive substance that causes addiction and dependence. The feeling of addiction and dependence on adolescents who still have unstable emotions and short-term thoughts causes an increase in alcohol consumption in adolescents. It is also a major cause of social chaos because alcohol can destroy self-control in a person. Someone who is addicted to drinking alcohol will get side effects in the form of organic mental disorders (GMOs). This makes the authors interested in researching the impact on the social behavior of adolescents who consume alcoholic beverages. The method used in this research is a case study. The results of this study are the factors that cause a teenager to consume alcohol, including escape, the media, the surrounding environment, wrong information, culture, and lack of understanding of religion as well as the social impact that occurs from consuming alcoholic beverages, which can be one of the causes of action. - negative actions even criminal acts.